Genetics professionals' perspectives on reporting incidental findings from clinical genome‐wide sequencing12. Issue 3 (7th February 2013) - Lohn, Zoe; Adam, Shelin; Birch, Patricia; Townsend, Anne; Friedman, Jan
Abstract Whole exome or whole genome analysis using massively parallel sequencing technologies will undoubtedly solve diagnostic dilemmas; however, incidental findings (IF) that may have medical and social implications will also be discovered. While there is consensus in the literature that analytically valid and medically actionable IF should be returned to patients if requested, there is debate regarding the return of other IF. There are currently no guidelines established for managing IF in the clinical context. We therefore distributed an online questionnaire to 496 geneticists and genetic counselors in Canada to explore this unresolved issue, and 210 professionals participated (response rate = 42%). The proportion of respondents who indicated that they would return IF to patients depended on the nature of the finding, ranging from 95% for information pertaining to a serious and treatable condition to 12% for information with only social implications (e.g., non‐paternity). There was a lack of consensus around the disclosure of certain IF such as genetic carrier status, especially for pediatric patients. The most important considerations identified as impacting IF disclosure included condition‐specific factors such as treatment availability, test accuracy, and evidence indicating pathogenicity. This is the first study to document the views of geneticists and genetic counselors in Canada towards the disclosure of IF, and represents a step towards evidence‐based guidelines for clinical genome‐wide sequencing investigations. © 2013 Wiley Periodicals, Inc.